The Epistemology of Sunnah as a Pillar of Transformative Curriculum in Islamic Education: A Thematic Study of Scientific Hadith: Epistemologi Sunnah sebagai Pilar Kurikulum Transformatif dalam Pendidikan Islam: Studi Tematik Hadis Keilmuan - Altsaury, Roychan Abdul Aziz; Rahmawati, Ana (Takwil: Journal of Quran and Hadith Studies, 2025)
Abstract: Islamic education plays a central role in shaping individual character and societal civilization, with the virtues of learning and teaching upheld as core values. These virtues are profoundly reflected in numerous hadiths of the Prophet Muhammad SAW, which encapsulate not only intellectual dimensions but also spiritual and ethical foundations. However, in contemporary educational practice, there exists a significant gap between the ideal values embodied in hadith and the implementation of curricula that tend to prioritize cognitive and instrumental outcomes. Moreover, academic studies that specifically explore educational hadiths through a thematic approach to address the demands of 21st-century education remain notably scarce. This condition underscores the urgency of systematically reexamining the prophetic traditions on the virtues of learning and teaching, in order to formulate a value-based framework that can be integrated into a transformative Islamic educational curriculum. This study aims to identify, classify, and analyze hadiths related to the virtues of seeking and imparting knowledge, and to explore their relevance in designing contemporary Islamic education curricula. The main focus is on integrating the spiritual, moral, and intellectual values found in hadith into both formal and non-formal education systems, especially in the context of digital-era challenges. Employing a qualitative approach with thematic (maudhu’i) analysis, this research draws upon authoritative hadith collections and is supported by contextual academic literature. The findings reveal that these prophetic traditions not only convey spiritual merit but also offer transformative educational philosophy. Their integration can serve as a foundation for curriculum development that simultaneously addresses cognitive, affective, and spiritual dimensions. This study provides practical implications for strengthening the role of hadith as a source of ethical guidance and visionary pedagogy in the advancement of Islamic education.